2019
DOI: 10.1080/1461670x.2019.1633946
|View full text |Cite
|
Sign up to set email alerts
|

Paywalls’ Impact on Local News Websites’ Traffic and Their Civic and Business Implications

Abstract: In an attempt to manage a looming revenue crisis in their transition from print to digital, many local newspapers have implemented user payment (paywalls) in their online editions. This paper asks what the business and civic implications of such introduction of user payment are. Comparing audience metrics on a sample of eight local news websites (four Norwegian,four Danish) for 52 weeks before and after paywall introduction, this study finds that the numbers of both pageviews and unique visitors decrease upon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 50 publications
0
14
0
5
Order By: Relevance
“…The introduction of paid content allows local newspapers to capitalize on niche content in local markets, differentiate high-and low-value content, and identify valuable readers in key segments without significant drops in reach (Olsen and Solvoll 2018b). Restricting access can also lead to "thinner" consumption of local news, less attachment to local newspapers, and readers seeking alternative news sources, particularly younger, less affluent readers with lower interest in news (Olsen and Solvoll 2018a), as well as decreased pageviews and unique visitors over time (Olsen, Kammer, and Solvoll 2020). Park, Fisher, and Lee (2021) found that interest in supporting local news was tied to consumers' sense of community belonging and trust in local news, while a willingness to pay for news was tied to content quality, unique content, and interactive features.…”
Section: The Role Of Paid Contentmentioning
confidence: 99%
“…The introduction of paid content allows local newspapers to capitalize on niche content in local markets, differentiate high-and low-value content, and identify valuable readers in key segments without significant drops in reach (Olsen and Solvoll 2018b). Restricting access can also lead to "thinner" consumption of local news, less attachment to local newspapers, and readers seeking alternative news sources, particularly younger, less affluent readers with lower interest in news (Olsen and Solvoll 2018a), as well as decreased pageviews and unique visitors over time (Olsen, Kammer, and Solvoll 2020). Park, Fisher, and Lee (2021) found that interest in supporting local news was tied to consumers' sense of community belonging and trust in local news, while a willingness to pay for news was tied to content quality, unique content, and interactive features.…”
Section: The Role Of Paid Contentmentioning
confidence: 99%
“…In line with these findings, Goyanes (2015) shows that US adults' willingness to pay for online local news increases with age. Therefore, delivering the value that customers require and thereby increasing their willingness to pay becomes a crucial factor that according to Olsen, Kammer, et al (2020) has to compensate for a decrease in online traffic due to hard or soft paywalls.…”
Section: Literature Review: Digital Transformation Of Local Mediamentioning
confidence: 99%
“…Regarding local media, we argue that public support instruments are potential external un-lock mechanisms. Two types of public support are differentiated: direct and indirect instruments (Nielsen and Linnebank 2011;K€ unzler et al 2013;Ali 2017;Harte, Howells, and Abingdon 2019;Olsen, Kammer, et al 2020;Murschetz 2020). While direct instruments support specific news organizations, indirect instruments support journalistic ecosystems.…”
Section: Literature Review: Digital Transformation Of Local Mediamentioning
confidence: 99%
“…La prensa tradicional ha tenido que adaptarse al impacto generado por el advenimiento y la masificación de internet, que ha cambiado los antiguos patrones de financiamiento y difusión (Luo, 2020). A la necesidad de digitalizarse, siguió una caída en los ingresos por publicidad, dado que la mayor parte de las entradas por publicidad en línea se las lleva Google o Facebook (Collins, 2011;Luo, 2020;Olsen et al, 2020). Esto condujo a recortes presupuestarios y de personal, y a la desaparición de gran parte de la prensa local en beneficio de las grandes corporaciones (Bethea, 2020;Catalan-Matamoros y Elías, 2020;Collins, 2011;Olsen et al, 2020).…”
Section: Crisis De Presupuesto Y Comercializaciónunclassified